THE USE OF BADE TUMPANG SOLAS IN THE NGABEN CEREMONY IN PURI AGUNG PELIATAN, PELIATAN VILLAGE, UBUD DISTRICT, GIANYAR REGENCY - Made Sri Putri Purnamawati (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Pitra Yadnya means sacred offerings to pitra or ancestral spirits and includes living parents. There is a uniqueness in carrying out the Ngaben ceremony, especially in Peliatan Village, which lies in the use of Bade Tumpang Solas itself, Bade Tumpang Solas is very rarely found and only certain people use it. In particular, the following research aims to achieve are to find out how the procession of using Bade Tumpang Solas at Puri Agung Peliatan, to find out what is the meaning of the use of Bade Tumpang Solas in the Ngaben ceremony at Puri Agung Peliatan, to find out the socio-religious and aesthetic values in the use of Bade Tumpang Solas in the Ngaben ceremony at Puri Agung Peliatan. The data was analyzed using qualitative method. Data collection in this study used several techniques such as: Observation, Interview, Literature review, Documentation. The result of this study is that the process of ngaben starting from choosing the day, making Bade and PeMelaspasan (ceremony). The meaning of using Bade Tumpang Solas in the Ngaben ceremony at Puri Agung Peliatan is as a symbol of the mountain. The socio-religious and aesthetic values contained in the use of Bade Tumpang Solas are: Religious values, the value of social solidarity, and aesthetic values.